Ferroelectric characteristics of SrBi4Ti4O15 thin films grown on Pt/Ti/SiO2/Si substrates by the soft chemical method - Simoes, A. Z.; Ramirez, M. A.; Riccardi, C. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
Ferroelectric SrBi4Ti4O15 thin films were successfully prepared on a Pt(111)/Ti/SiO2/Si(100) substrate for the first time by spin coating, using the polymeric precursor method. X-ray diffraction patterns of the films indicate that they are polycrystalline in nature. Atomic force microscopy (AFM) analyses showed that the surface of these films is smooth, dense and crack-free with low surface roughness (6.4 nm). At room temperature and at a frequency of 1 MHz, the dielectric constant and the dissipation factor were, respectively, 150 and 0.022. The C-V characteristics of perovskite thin film prepared at low temperature show normal ferrolectric behaviour. The remanent polarization and coercive field for the films deposited were 5.4 mu C/cm(2) and 8 5 kV/cm, respectively. All the capacitors showed good polarization fatigue characteristics at least up to 1 x 10(10) bipolar pulse cycles indicating that SrBi4Ti4O15 thin films can be a promising material for use in nonvolatile memories. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: thin films; atomic force microscopy; dielectric properties; fatigue